Problems of law enforcement against civil servants involved in corruption cases of the complete systematic land program in Palembang city - Rillo Waskitha Sandi Wiyata; Hambali Yusuf; Serlika Aprita; Abdul Latif Mahfuz (The International Journal of Politics and Sociology Research, 2023)
This paper explains, Corruption comes from the Latin Corruption from the verb corrumpere means rotten, damaged, shaken, overthrown, bribed. According to Transparency International, it is the behavior of public servants, both politicians/politicians and civil servants, who illegally and illegally enrich themselves or their families by abusing the public power entrusted to them. The research method used is empirical legal research or sociological research that prioritizes field data (field research) which is evaluative in nature with the aim of assessing the implementation of a legal regulation. The formulation of the problem is the factors that influence law enforcement against civil servants involved in corruption cases of the Complete Systematic Land Program (PTSL) in Palembang City. The conclusion is that the factors that influence the prosecution of officials involved in corruption cases of the Complete Systematic Land Program (PTSL) in Palembang City, namely the legal regulation factor itself, due to the absence of supporting instruments in the form of laws and regulations that implement the criminal act of corruption is not running properly.